2006
DOI: 10.1177/08830738060210010801
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Meningiomas in Children: Report of 27 New Cases and Critical Analysis of 440 Cases Reported in the Literature

Abstract: We accumulated 440 cases of intracranial meningiomas in patients under 16 years of age, and another 27 personal. This review confirms the existence of specific clinical features of spontaneous and radiation-induced meningioma in children. In addition, we discuss various points that suggest a more aggressive behavior of meningiomas in children than in adults. (J Child Neurol 2006;21:31-36).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 109 publications
(163 reference statements)
0
49
1
3
Order By: Relevance
“…5,6 The frequency of intraventricular meningiomas in children is 12%, whereas it ranges from 0.5% to 4.5% in adults. 7 Intraventricular meningiomas most often develop in the trigone of the lateral ventricles, with an unexplained predilection for the left lateral ventricle. Approximately 15% arise in the third ventricle, which is more common in childhood, and only about 5% arise in the fourth ventricle.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 The frequency of intraventricular meningiomas in children is 12%, whereas it ranges from 0.5% to 4.5% in adults. 7 Intraventricular meningiomas most often develop in the trigone of the lateral ventricles, with an unexplained predilection for the left lateral ventricle. Approximately 15% arise in the third ventricle, which is more common in childhood, and only about 5% arise in the fourth ventricle.…”
Section: Discussionmentioning
confidence: 99%
“…The long term prognosis for surgically treated menigiomas in children is controvertial, but according to the conclusion from the most recent and largest review about intracranial meningiomas in children, made by Caroli et al in 2006 33 , who colleted 440 cases reported in the literature, children like adults, with typical meningiomas and complete resections show good outcome.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, we found that the average duration of symptoms with hemangiopericytoma was 4.0 months, whereas in pediatric patients, the average duration with meningioma was 1.2 years. 18 Besides intracranial meningioma, the following tumors should be differentiated. 1) Glioblastoma.…”
Section: Discussionmentioning
confidence: 99%